Social Cultural Impact Of Tourist Interaction With Local Community In Lake Toba Area - Siti Purnama Sari (International Journal of Cultural and Social Science, 2020)
Lake Toba is a tourism area in North Sumatra, where interactionsbetween tourists and local communities have an impact on thegrowth of tourism life. The form of interaction varies based on themotivation and actor of the interaction. The first is for businesstransactions, tourists as consumers and business actors as providers.The second occurs when tourists and the public meet at the sametourist attraction, namely a cafe restaurant with the motivation offriendship, finance, and romance. The next interaction occurs whenboth parties seek information, both about tourism, culture andpersonal data. Interactions for transacting tourism occur more often,followed by interactions when tourists and local people meet at cafesor restaurants on Lake Toba. Interactions can then be distinguishedbetween tourists and working people, and with non-working people.Socio-cultural impacts due to these interactions includedemonstrative effects, changes in social values, for example: normschange views on the relationship between men and women,materialistic nature and cultural values in performing arts, culturallearning and tourism culture.